DEVS 형식론 기반의 선박 항해 모델링 및 시뮬레이션 (II) : COLREG 기반 선박 충돌회피 시뮬레이션을 통한 사례연구 - 황훈규(Hun-Gyu Hwang); 우상민(Sang-Min Woo); 이장세(Jang-Se Lee) (한국정보통신학회논문지, 2019)
Recently, many researches have been under way to develop systems (services) to support the safety navigation of ships, and in these studies, common difficulties have been encountered in assessing the usefulness and effectiveness of the developed system. To solve these problems, we propose the DEVS-based ship navigation modeling and simulation technique. Following the preceding study, we analyze the COLREG rules and reflected to officer and helmsman agent models for decision making. Also we propose estimation and interpolation techniques to adopt the motion characteristics of the actual vessel to simulation. In addition, we implement the navigation simulation system to reflect the designed proposed methods, and we present five-scenarios to verify the developed simulation system. And we conduct simulations according to each scenario and the results were reconstructed. The simulation results confirm that the components modelled in each scenario enable to operate according to the navigation relationships. 최근, 선박의 안전항해를 지원하기 위한 시스템(서비스)의 개발을 위해 여러 연구가 진행되고 있으며, 이들 연구에서는 개발한 시스템의 유용성 검증 및 효과도 평가에 공통적인 어려움을 겪고 있다. 본 논문에서는 이러한 문제를 해결하기 위해 DEVS 형식론 기반 선박 항해 모델링 및 시뮬레이션 기법을 제안한다. 선행연구에 이어 국제해상충돌예방규칙과 관련된 내용을 분석 및 도출하여 의사결정을 위한 항해사 및 조타수 에이전트를 모델링하고, 실제 선박의 운동특성을 반영하기 위한 추정 및 보간 기법을 제안한다. 또한, 설계한 내용을 반영하여 선박 항해 시뮬레이션 시스템을 구현하고, 개발한 시스템의 유용성을 검증하기 위한 다섯 가지 충돌회피 시나리오를 개발한다. 그 후, 각 시나리오에 따른 시뮬레이션을 수행하고 결과를 재구성하여 제시한다. 이를 통해 시뮬레이션 아키텍처 내에서 선박 구성요소 및 에이전트 모델이 유기적으로 결합하여 충돌회피 의사결정 및 항해 시뮬레이션이 가능함을 확인하였다.